Inovasi Media Pembelajaran Sosiologi Melalui Video Pembelajaran Bagi Guru SMA - Januarti, Nur Endah; Pratiwi, Poerwanti Hadi; Hendrastomo, Grendi (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2018)
The community service is training for Sociology’s teachers in Bantul. This activity is to equip teachers about learning media knowledge and application of instructional media. There are many activities which are conducted to be applied and practiced in sociology classes so that sociology learning becomes interesting and not boring for learners. Training is done through varied lecture methods, discussions, and frequently asked questions. Various lecture methods are used to convey concepts that are important to be understood and mastered by the participants. The material given is the type and characteristics of instructional media. Learning media is devoted to learning videos. Question and discussion methods to provide opportunities for participants to consult in understanding the making of learning media and video learning. Making learning videos using the Windows Movie Maker program. From the training process the teacher is able to produce the learning video of class X, XI, XII. Video learning can be used in learning. Activity is supported by several factors. These factors are First, the existence of adequate experts from the Department of Education Sociology FIS UNY, the two participants are enthusiastic, the three principals who support the activities, and the four fa. The obstacles faced were the different basic abilities of participants and time management participants due to the various tasks of the school that caused their focus not to total training materials. Keywords :Learning innovation, Video learning, Sociology, Senior high school